Pengujian Kekuatan Bending dan Impak Komposit Sandwich Serat Gelas dengan Inti Kayu Balsa - Agus Dani; Nurlia Pramita Sari; Fauzan Baananto; Sulistyono Sulistyono (Universitas Islam Raden Rahmat, Malang, 2024)
The strength of a sandwich composite structure is influenced by the mechanical properties of the skin and core, the thickness of the skin and core, and the strength of the bond between the skin and core. Balsa wood is a suitable core material for sandwich composite applications due to its high strength-to-weight ratio. Another advantage of balsa wood is that it is a widely available and relatively inexpensive material. In this study, sandwich composites with glass fiber skin and balsa wood core were made using the hand lay-up method, using epoxy resin. Variations in the direction of woven fibers (45o/45o) and straight (0o/90o) and variations in the weight of the weave 200 GSM, 400 GSM, and 600 GSM were tested to determine the mechanical bonding. Mechanical bonding testing was carried out using the three-point bending test method (three-point bending) and impact testing. The results showed that the orientation of the fibers affects the flexural stress and impact of the sandwich composite. Straight fiber orientation has higher stress and impact values than diagonal orientation. The highest stress value was at 400 GSM straight fiber orientation variation with a flexural stress value of 149.53MPa and had the highest impact value of 0.052 Joule/mm